A New Approach to Estimate Real-Time Traveling Speed with Accelerometer - Xiaojie Zong; Xiangji Wen (International Journal of Distributed Sensor Networks)
In order to estimate the traveling speed, three parts are mainly described in this paper, including coordinate system relationship establishment between vehicle and smartphone, proper character extraction of acceleration in the vehicle coordinate system and model training process.